Involvement of PUF60 in Transcriptional and Post-transcriptional Regulation of Hepatitis B Virus Pregenomic RNA Expression. Issue 1 (December 2017) - Sun, Suofeng; Nakashima, Kenji; Ito, Masahiko; Li, Yuan; Chida, Takeshi; Takahashi, Hirotaka; Watashi, Koichi; Sawasaki, Tatsuya; Wakita, Takaji; Suzuki, Tetsuro
Abstract Here we identified PUF60, a splicing factor and a U2 small nuclear ribonucleoprotein auxiliary factor, as a versatile regulator of transcriptional and post-transcriptional steps in expression of hepatitis B virus (HBV) 3.5 kb, precore plus pregenomic RNA. We demonstrate that PUF60 is involved in: 1) up-regulation of core promoter activity through its interaction with transcription factor TCF7L2, 2) promotion of 3.5 kb RNA degradation and 3) suppression of 3.5 kb RNA splicing. When the 1.24-fold HBV genome was introduced into cells with the PUF60-expression plasmid, the 3.5 kb RNA level was higher at days 1–2 post-transfection but declined thereafter in PUF60-expressing cells compared to viral replication control cells. Deletion analyses showed that the second and first RNA recognition motifs (RRMs) within PUF60 are responsible for core promoter activation and RNA degradation, respectively. Expression of PUF60 mutant deleting the first RRM led to higher HBV production. To our knowledge, this is the first to identify a host factor involved in not only positively regulating viral gene expression but also negative regulation of the same viral life cycle. Functional linkage between transcriptional and post-transcriptional controls during viral replication might be involved in mechanisms for intracellular antiviral defense and viral persistence.